HARMONISASI PENGATURAN UPAYA ADMINISTRATIF DALAM PENYELESAIAN SENGKETA ADMINISTRASI NEGARA DARI PERSPEKTIF TEORI AL-ADALAH DAN AL-SHURA - Hadisiswati, Indri; ., Darmawan (UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
The regulation regarding administrative efforts in resolving state administrative disputes is governed by two different legal foundations. There is a dualism of opinion regarding the necessity of administrative efforts before filing a lawsuit in court, whether it is imperative or facultative, based on the provisions of these two legal foundations, namely the State Administrative Court Law and the General Administrative Procedure Law. This legal issue will be examined through normative legal research, The study concludes that administrative efforts in resolving state administrative disputes are facultative as long as they are not explicitly regulated in sectoral laws. The facultative nature of these administrative efforts also requires simplification in resolving administrative disputes. This simplification can be achieved by limiting the process to two levels of administrative court examinations, ending with a review and decision by the Supreme Court. Harmonious administrative arrangements in resolving state administrative disputes must consider the fundamental principles of Islamic law, such as al-Adalah (Justice) and al-Shura (Deliberation). Justice ensures that decisions taken fairly fulfill the rights and obligations of the involved parties, while deliberation emphasizes the importance of collaboration and participation in decision-making, allowing for outcomes that are more widely accepted by all parties.